Phantosmia and Dysgeusia following Endoscopic Transcribriform Approaches to Olfactory Groove Meningiomas - Venteicher, Andrew S.; Kumar, Jay I.; Murphy, Emma A.; Gray, Stacey T.; Holbrook, Eric H.; Curry, William T. (Journal of Neurological Surgery Part B: Skull Base, 2017)
The endoscopic, endonasal transcribriform approach (EETA) is an important technique used to directly access the anterior skull base and is increasingly being used in the management of olfactory groove meningiomas (OGMs). As this approach requires removal of the cribriform plate and olfactory epithelium en route to the tumor, patients are anosmic postoperatively. Here, we report the development of phantosmia and dysgeusia in two patients who underwent EETAs for OGMs, which has not yet been reported in the literature. We hypothesize that phantosmia and dysgeusia may result from aberrant neuronal signals or misinterpretation centrally from the remaining distal portions of the olfactory and taste pathways. Since EETAs are newer than traditional open craniotomy-based techniques, reporting these outcomes will be important to appropriately counsel patients preoperatively.
Keywords: olfactory groove meningioma; transcribriform; phantosmia; dysgeusia; anterior skull base